Neonates with Jaundice A Clinical Profile - Davis Manuel; Shajahan R A (Asian Journal of Clinical Pediatrics and Neonatology, 2020)
Background: In the first week of child birth, neonatal jaundice is the most common problem which leads to delayed hospital discharge and re-admissions. Recognising early neonatal hyperbilirubenemia plays a pivotal role in preventing serious complications. The aim of this study was to study the clinical profile and the aetiological factors leading to neonatal jaundice in rural areas.Subject and Method:This study is a prospective observational study  conducted in neonatal intensive care unit (NICU) and post natal ward . This study was conducted during the period of February 2017 to July 2017. Total 400 neonates were admitted in NICU and post natal ward during this period. Out of them, 100 newborns were having jaundice (Serum bilirubin > 10 mg/dl). 100 cases in total were enrolled in the study. Result:In this study,out of 100 neonates, 70% were males and 30% were females. , 92 were born at term (92%) and remaining 10 were preterm babies (10%). Physiological jaundice constituted 45%, followed by ABO incompatibility constituted 25%, followed by sepsis(1%), Rh incompatibility (8%), idioapathy (8%), prematurity (5%), cephalhematoma (4%), breast feeding (2%), haemolytic anemia (2%) were diagnosed as hereditary spherocytosis. Conclusion:Physiological jaundice is the most common cause of neonatal jaundice followed by ABO incompatibility, sepsis, Rh incompatibility and idiopathic cases. Cephalhematoma, breast feeding jaundice and haemolytic anaemia are the less common causes. Hence, it is required to monitor neonates more appropriately and accurately.